Kidney disorders in patients with type 2 diabetes: The potential role of the A1166C (rs5186) angiotensin II type 1 receptor gene polymorphism - Andriy Nesen; Polina Semenovykh; Kateryna Savicheva; Valentina Galchinska; Volodymyr Chernyshov; Volodymyr Shkapo (Ukrainian Journal of Nephrology and Dialysis, 2025)
The study aimed to identify a possible association between the A1166C (rs5186) polymorphism of the AT1R gene and markers of kidney function in patients with type 2 diabetes and nephropathy.Methods. The study involved 194 patients with DN: 108 women and 86 men. The patients' ages ranged from 43 to 80 years, with an average age of (56.32±3.21) years. The control group consisted of 48 healthy individuals. Deoxyribonucleic acids (DNA) were extracted from blood using a standard method with the “NeoPrep50” reagent kit (Neogen, Ukraine) according to the manufacturer’s instructions. Genotyping of the A1166C (rs5186) polymorphism of the AT1R gene was performed using TaqMan technology with the TaqMan® Fast Universal PCR Master Mix and TaqMan® SNP Assay kits. Statistical analysis of genetic associations was conducted using the SNP Stats program.Results. Data analysis using SNPStats revealed a significant difference in genotype and allele frequencies of the studied polymorphism in the group of patients with diabetic nephropathy (DN) compared to the control group, corresponding to: Codominant inheritance model: OR 0.31 (0.12–0.81); p=0.044; Dominant inheritance model: OR 0.36 (0.15–0.89); p=0.024; Overdominant inheritance model: OR 0.32 (0.12–0.80); p=0.012. Patients with DN who carried the C/C genotype of the rs5186 polymorphism of the AT1R gene demonstrated significantly higher levels of creatinine (130.60 [46.44–214.76] mg/L), urea (12.44 [2.55–27.43] mg/L), and lower glomerular filtration rate (GFR) (54.20 [25.19–83.21] mL/min/1.73m²) compared to heterozygous A/C and homozygous A/A carriers. Patients with DN homozygous for the C allele of the AT1R gene had significantly higher urinary albumin levels (110.35 [12.81–233.50] μg/mL) compared to A/C heterozygotes (49.99 [22.41–77.58] μg/mL). The highest albumin-to-creatinine ratio in urine was observed in DN patients homozygous for the C allele of the AT1R gene (0.59 [0.08–1.10]), compared to A/C heterozygotes (0.44 [0.16–0.72]), p<0.05, and A/A homozygotes (0.27 [0.19–0.35]), p<0.05.Conclusions. Patients with DN who are homozygous for the C allele of the AT1R gene exhibit significantly higher levels of creatinine, urea, urinary albumin, and the albumin-to-creatinine ratio, as well as lower GFR, compared to A/C heterozygotes (p<0.05) and A/A homozygotes. These findings demonstrate the unequivocally negative impact of the C allele on kidney functional status in this patient group.